2014
DOI: 10.1371/journal.pcbi.1003764
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Nonlinearities Reduce Network Size Requirements and Mediate ON and OFF States of Persistent Activity in a PFC Microcircuit Model

Abstract: Technological advances have unraveled the existence of small clusters of co-active neurons in the neocortex. The functional implications of these microcircuits are in large part unexplored. Using a heavily constrained biophysical model of a L5 PFC microcircuit, we recently showed that these structures act as tunable modules of persistent activity, the cellular correlate of working memory. Here, we investigate the mechanisms that underlie persistent activity emergence (ON) and termination (OFF) and search for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Moreover, apical dendrite ablation eliminates the contribution of regenerative potentials on distal dendrites 30 , which have been observed during complex behavioral task in vivo 31 or L1 stimulation in vitro 32 . Our results suggest that neurons can still compute orientation tuning without those regenerative dendritic electrical events, favoring a feedforward model for orientation selectivity 33,34 . Computational modeling confirmed that basal dendritic input is dominant over a wide range of synaptic input parameters.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, apical dendrite ablation eliminates the contribution of regenerative potentials on distal dendrites 30 , which have been observed during complex behavioral task in vivo 31 or L1 stimulation in vitro 32 . Our results suggest that neurons can still compute orientation tuning without those regenerative dendritic electrical events, favoring a feedforward model for orientation selectivity 33,34 . Computational modeling confirmed that basal dendritic input is dominant over a wide range of synaptic input parameters.…”
Section: Discussionmentioning
confidence: 73%
“…In the current study, we see how a persistent activity attractor landscape can be formed by complementing the effects of mutual excitation with the multiple complementary effects of excitatory and inhibitory interactions across cortical layers (Papoutsi et al, 2013, Papoutsi et al, 2014, Nelson et al, 2003, Marder et al, 1996). By contrast, Wang’s “bump attractor” network model was based on localized connectivity in a single layer of integrate-and-fire neurons (Compte et al, 2000, Wang, 2001).…”
Section: Discussionmentioning
confidence: 89%
“…Dependent on the spatial arrangement of incoming inputs, the nonlinear integration properties of NMDARs can rapidly shift synaptic efficacies and enable the network to differentially integrate information for short periods of time (Buzsáki, 2010; Stokes, 2015). This is based on several lines of evidence indicating that NMDA receptors are important for PFC function (Lisman et al, 1998; Papoutsi et al, 2014; Wang, 1999; Wang et al, 2013). Furthermore, maximal exploitation of NMDA non-linearities is achieved by connecting subsets of neurons in a clustered, hyper-reciprocal manner, as evidenced in the PFC anatomy (Wang et al, 2006), and previously hypothesized to be beneficial for memory (Brunel, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…adaptive coding (Stokes et al, 2013). In support of this hypothesis, NMDA-dependent dendritic non-linearities have been shown to underlie the expression of memory states in computational models of small cell assemblies (Papoutsi et al, 2014, 2017).…”
Section: Introductionmentioning
confidence: 87%